2014
DOI: 10.1002/2013gl058770
|View full text |Cite
|
Sign up to set email alerts
|

Observation of mountain lee waves with MODIS NIR column water vapor

Abstract: Mountain lee waves have been previously observed in data from the Moderate Resolution Imaging Spectroradiometer (MODIS) "water vapor" 6.7 μm channel which has a typical peak sensitivity at 550 hPa in the free troposphere. This paper reports the first observation of mountain waves generated by the Appalachian Mountains in the MODIS total column water vapor (CWV) product derived from near-infrared (NIR) (0.94 μm) measurements, which indicate perturbations very close to the surface. The CWV waves are usually obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…A 10% systematic negative bias is observed for Aqua retrievals for CWV > 2.0 cm (Figure b ii ), while Terra shows none trend regardless the concentration (Figure a ii ). Given the different sensitivity of NIR channels [ Gao and Kaufman , ], the algorithm computes the average of water vapor based on weighting functions stored in the look‐up table, which depends on atmosphere condition (“dry” or “humid”) (see more details in Lyapustin et al []). Thus, described negative bias should be related to calibration of the least absorbing channel (B17) of MODIS Aqua which has the highest weight in humid conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A 10% systematic negative bias is observed for Aqua retrievals for CWV > 2.0 cm (Figure b ii ), while Terra shows none trend regardless the concentration (Figure a ii ). Given the different sensitivity of NIR channels [ Gao and Kaufman , ], the algorithm computes the average of water vapor based on weighting functions stored in the look‐up table, which depends on atmosphere condition (“dry” or “humid”) (see more details in Lyapustin et al []). Thus, described negative bias should be related to calibration of the least absorbing channel (B17) of MODIS Aqua which has the highest weight in humid conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Once the MODIS reflectance is gridded and split into both 600 × 600 km tiles and 25 × 25 km blocks, they are placed in a queue of 4–16 days. Water vapor is first derived from MODIS near‐IR bands [ Lyapustin et al ., ] by using a modification of the algorithm described in Gao and Kaufman []. An internal cloud mask uses spectral reflectance and brightness temperature tests similar to the operational MODIS cloud mask algorithm [ Frey et al ., ], along with the reference clear‐sky image developed by using a covariance‐based algorithm.…”
Section: Datamentioning
confidence: 99%
“…This is consistent with Nieto et al (2010) who also found poorer prediction of e a when modelled on a daily-time-step, due to the variability of e a in the atmosphere during the day. Additionally, e a performance may have been affected by a lower accuracy of the MOD05 product over parts of Australia, which is reportedly due to iron-rich soils affecting spectral reflectance (Lyapustin et al, 2014). Given this, the strategy of modelling D based Table 3 Validation of MODIS meteorological variables against corresponding on-ground observations measured over one year at each of the flux tower sites.…”
Section: Performance Of Remotely Sensed Vapour Pressure Deficit Modelsmentioning
confidence: 99%